The escape motivation of emerging market multinational enterprises - Alvaro Cuervo-Cazurra; Ravi Ramamurti (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
The authors argue that FDI by emerging-market firms in advanced economies is motivated not just by "pull" factors, such as the host country's large market or technical talent, but also by "push" factors, such as the home country's weak institutions and reputation. We explain the latter, which we call "escape FDI."
Keywords: 330